REFLECTION TO GUIDE MEDICAL STUDENTS’ SELFINTROSPECTION AND DEVELOPMENT: A QUALITATIVE REPORT - Imelda Ritunga; Etha Rambung (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Reflection is needed by the doctor in interpreting his experience, realizing its limitations so that it will be lifelong learning. In medical learning, self reflection can motivate students to realize their limitations and learn better. The purpose of this study is to explore the experiences of students in reflection learning. Methods: the research method uses a qualitative type with the research subjects being 15 first-year medical students. Reflection is taught at the beginning of education and is practiced in innovation design courses by providing weekly writing self-reflection assignments. The experience of writing self reflection was explored through group interviews (FGD) and in-depth interviews. Open questions are given to students, the results of interviews are verbatim and coding. This study has obtained ethical clearance.Results: the results of the study were divided into 5 themes: perception, self-awareness, future improvement, rules, and other. Participants expressed pleasure in self-reflection, useful for self-reflection, and future improvement. Future improvements vary from no change to the change in perspective and even change in action, which is more disciplined. Rules for a minimum number of words in self-reflection assignments are things are not fun to participants and can make writing blindly. The frequency of writing self-reflection carried out every week is felt to burden the participants. Other draw on participants' statements regarding activities to write reflections that are felt to be useful as part of learning as a writer.Conclusion: learners' perceptions of reflection learning are fun and useful, but students complain about the rules for reflection assignments so design reflection should relevant and contextual.